2014
DOI: 10.1017/s1751731114001335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cinnamon (Cinnamomum zeylanicum) essential oil supplementation on lamb growth performance and meat quality characteristics

Abstract: A trial was conducted to examine the effect of cinnamon essential oil supplementation on lamb growth performance and meat quality. Sixteen male lambs were randomly assigned to two groups. The first group served as control and was given a basal diet, and the second group was given the same diet supplemented with cinnamon oil (1 ml/kg of concentrated feed) for 35 days. Incorporation of cinnamon oil did not affect growth performance (P > 0.05). Meat pH, colour, water-holding capacity, shear force, intramuscular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…The presence of cinnamaldehyde and eugenol may enhance the antibacterial effect, as suggested by Burt (2004) . Essential oils from A. triphylla , Cinnamomum citratus , L. cubeba , and M. piperita showed no relevant activity against Salmonella ; however, other authors have described in vitro antibacterial activity of EO from S. aromaticum and C. zeylanicum against paratyphoid Salmonella strains ( Simitzis et al., 2014 , Thanissery et al., 2014 , Abbes et al., 2018 ). It has been reported that the EO of cinnamon ( C. zeylanicum ) and thyme ( T. vulgaris ) produced the highest activity, with 22.5–38.5 mm inhibition zones against 5 Salmonella serotypes ( Olaimat et al., 2019 ).…”
Section: Resultsmentioning
confidence: 93%
“…The presence of cinnamaldehyde and eugenol may enhance the antibacterial effect, as suggested by Burt (2004) . Essential oils from A. triphylla , Cinnamomum citratus , L. cubeba , and M. piperita showed no relevant activity against Salmonella ; however, other authors have described in vitro antibacterial activity of EO from S. aromaticum and C. zeylanicum against paratyphoid Salmonella strains ( Simitzis et al., 2014 , Thanissery et al., 2014 , Abbes et al., 2018 ). It has been reported that the EO of cinnamon ( C. zeylanicum ) and thyme ( T. vulgaris ) produced the highest activity, with 22.5–38.5 mm inhibition zones against 5 Salmonella serotypes ( Olaimat et al., 2019 ).…”
Section: Resultsmentioning
confidence: 93%
“…EOs from A. triphylla , C. citratus , L. cubeba and M. piperita showed no relevant activity against Salmonella . Other authors reported in vitro antibacterial activity of S. aromaticum and C. zeylanicum EOs against paratyphoid Salmonella strains [15,16,17]. However, our study evaluated the action of different EOs versus several S. Enteritidis and S. Typhimurium strains isolated from poultry, whereas very scant data about the activity of EOs from A. triphylla , C. citratus , L. cubeba and M. piperita against Salmonella are available in literature [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Gois et al (2017) found that the oxidation of pork meat lipids was reduced by including red pepper essential oil. Simitzis et al (2014) reported that dietary cinnamon essential oil supplementation in lambs also reduced MDA concentration in muscle. Similarly to previous studies, our research showed that dietary PEO supplementation of finishing pigs significantly decreased the MDA content of longissimus dorsi , and meanwhile, remarkably improved the activities of T‐AOC and T‐SOD of longissimus dorsi .…”
Section: Discussionmentioning
confidence: 99%